Micro RNA expresados en la progresión del cáncer escamocelular de cavidad oral revisión sistemática (2021)
For the development of cancer, the tumor needs nutrients and oxygen for growth, which initially occurs through passive diffusion, but as its diameter increases it requires be nourished through new blood vessels; That is why angiogenesis is essential for uncontrolled growth of tumors.